Heart–brain interactions in cardiac arrhythmia. Issue 9 (1st March 2011) - Taggart, P; Critchley, H; Lambiase, P D
Abstract : This review examines current knowledge of the effects of higher brain centres and autonomic control loops on the heart with particular relevance to arrhythmogenesis. There is now substantial evidence that higher brain function (cortex), the brain stem and autonomic nerves affect cardiac electrophysiology and arrhythmia, and that these may function as an interactive system. The roles of mental stress and emotion in arrhythmogenesis and sudden cardiac death are no longer confined to the realms of anecdote. Advances in molecular cardiology have identified cardiac cellular ion channel mutations conferring vulnerability to arrhythmic death at the myocardial level. Indeed, specific channelopathies such as long QT syndrome and Brugada syndrome are selectively sensitive to either sympathetic or vagal stimulation. There is increasing evidence that afferent feedback from the heart to the higher centres may affect efferent input to the heart and modulate the cardiac electrophysiology. The new era of functional neuroimaging has identified the central neural circuitry in this brain-heart axis. Since precipitants of sudden fatal arrhythmia are frequently environmental and behavioural, central pathways translating stress into autonomic effects on the heart might be considered as therapeutic targets. These brain-heart interactions help explain the apparent randomness of sudden cardiac events and provide new insights into future novel therapies to prevent sudden death.